Pembuatan dan Pengelolaan Website di MA Mathlabul Huda - Muhammad Zaki Ikhsani; Feby Windi Damayanti; Saffana Assani'; Hermanto Hermanto (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2021)
MA Mathlabul Huda is one of the madrasas that still uses manual methods in disseminating information to the wider community. The school must inform this by distributing posters / banners in several areas close to the madrasah so that it requires fast, precise and accessible information media for the wider community. The purpose of this service is to create a website to help solve problems that exist in MA Mathlabul Huda. The method used in this case is the SDLC method by analyzing the data obtained from the madrasah. The design used to create a madrasah website uses the PHP programming language and the Codeigniter framework. The result of this dedication is a madrasah website that can be accessed by the wider community.